Haematological features in Paediatric patients on second line Highly Active Antiretroviral Therapy in Zimbabwe. - M, Madzivire; G, Chimhini; V, Chikwasha; A, Mandisodza (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Human immunodeficiency virus/acquired immune deficiency syndromes (HIV/AIDS) is still a public health challenge globally, with over 3 million children living with HIV/AIDS. Its treatment in children has both positive and negative effects. Haematological abnormalities account for most causes of deaths associated with HIV infection and its treatment. Highly active antiretroviral therapy (HAART) is now recommended as the standard form of care for people living with HIV/AIDS. This has particularly improved the quality of life of children with the condition. However, HAART regimens are often associated with unfavourable drug reactions which may be life-threatening.Objective: The major objective was to determine the effects of second line HAART combinations on haematological parameters in children living with HIV/AIDS.Materials and Methods: A cross sectional clinical and laboratory based prospective study on the haematological manifestation of children on different combinations of HAART regimens was carried out at Harare Central Hospital from January to April 2017.Results: A total of 97 EDTA blood samples from HIV paediatric patients on second line HAART treatment were analyzed for full blood count. Forty-four (45.4%) and 53 (54.6%) of them were females and males respectively. The four most frequent haematological abnormalities were neutropaenia (69.1%), leukopaenia (46.4%), anaemia (30.9%) and thrombocytosis (30.9%). The anaemia was of varying degrees of morphological classification and it was mainly caused by TDF-based combinations. The most common morphological classifications were normocytic normochromic anaemia (61.5%), microcytic hypochromic (26.9%) and macrocytic normochromic (7.7%). TDF/3TC/ATV/r (47.4%), ABC/3TC/LPV/r (18.6%), AZT/3TC/ATV/r (14.4%) and AZT/DDI/LPV/r (12.4%) were the most prescribed second line HAART combinations. Most haematological abnormalities were found to be commonly associated with TDF/3TC/LPV/r and AZT/3TC/ATV/r combinations.Conclusions: It can be concluded that haematological abnormalities were also present in paediatric HIV positive patients on second line HAART. The abnormalities were similar to those found in children on first line HAART, although anaemia was nearly twice that found in first line HAART.